Impact of radiocontrast media on microscopic urine morphology and output in children following cardiac catheterization - Ketut Indah Karina Mahardika; Putu Andrie Setiawan; Ni Putu Veny Kartika Yantie; Eka Gunawijaya (Pediatric Sciences Journal, 2026)
Background: The incidence of contrast-induced acute kidney injury (CI-AKI) was relatively high, especially in lower-income countries following cardiac catheterization. Urine morphology outperforms serum creatinine as an early, more specific, and cost-effective marker for detecting and differentiating CI-AKI. Urine output (UO) is also a cost-effective marker capable of detecting early CI-AKI. This study aims to determine differences in urine morphology and UO in pediatric patients pre- and post-cardiac catheterization, including subgroup analysis based on contrast type. Methods: A one-group pre-post experimental study from pediatric congenital heart disease (CHD) diagnosed by echocardiography patients aged 0-18 years, who underwent cardiac catheterization at a tertiary referral hospital in Bali (June-December 2025). Urine samples for urinalysis were obtained 2-12 hours before and 12-48 hours after the intervention. Fluid balance and urine output were collected using a urine bag or pediatric urine collector and totaled over 24 hours, 2-12 hours before and 24 hours after contrast administration. Urinalysis was analyzed using standard urine microscopy for morphology at a standardized private clinical laboratory. Data were analyzed using SPSS version 29.0. Results: A total of 43 pediatric patients who underwent cardiac catheterization; 3 declined participation; 40 eligible subjects. Urine morphology findings were not significantly different pre- and post-catheterization (McNemar exact test, p = 0.25, CI 95%). Urine output (mL/kg/hour) was significantly different and higher post-catheterization (Wilcoxon signed-ranks test, Z = −3.105, p = 0.002). There were significant differences in urine output between pre-and-post catheterization in Iohexol (p=0.004) but slightly not significant in Iopromide group (p=0.051). The increase in UO levels in the Iohexol group is significantly (p=0.042) higher than in the Iopromide group. Conclusion: No significant changes in urine morphology were observed pre-and-post catheterization. There is a significant change in urine output, which increased significantly after cardiac catheterization.